Model Pengelolaan Repository Institusi dalam Mendukung Diseminasi Penelitian Perguruan Tinggi (Studi Kasus di Universitas Mataram) - Ridwan; Susilawati, Hirma; Soadikin, Muhammad (UPT Perpustakaan UIN Alauddin Makassar, 2025)
University libraries have transformed with information technology, one of which is through Institutional Repositories that manage the scientific works of the academic community. This study aims to determine the management model of the Institutional Repository at the University of Mataram. The research method used is descriptive qualitative, with informants from the IT Division, IT Staff, Circulation Staff, as well as Processing and Technical Service Staff of the UPT Library of the University of Mataram. Data was collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The study results indicate that the repository management has been implemented effectively through planning, organizing, execution, as well as monitoring and evaluation stages. Planning includes benchmarking, human resource management, infrastructure planning, and content management. Organization is divided into human resource management and library material management. Implementation consists of deposit and service activities, while evaluation is carried out periodically and incidentally.The implications of this research can serve as an evaluation material for university library managers to develop repository management and as a reference for future research on institutional repository management.